THE CULTURAL VALUES OF TENGKO SITURU’ IN ENGLISH LANGUAGE TEACHING AT SMK NEGERI 1 TORAJA UTARA - Viktor Sumarlata; Rachel; Yizrel Nani Sallata; Dan Mangoki (FKIP Unismuh Makassar, 2023)
The purpose of this study was to determine the cultural value of tengko situru' (togetherness) in learning English. It is described in previous research that there is a close relationship between character education, values and culture, where value education cannot be separated from character education as well as culture which is one aspect formation of character education. This research uses descriptive qualitative method. The subjects in this study were four English teachers at SMK Negeri 1 Toraja Utara. The results of the research show that in the process of learning English the teachers introduce and apply the cultural values of tengko situru' in learning English. This can be seen from the interaction of students during the learning process.